Listeriosis: A Farm-to-Table Foodborne Disease - Alkuwaity, Khalil (Journal of King Abdulaziz University: Medical Sciences, 2024)
Foodborne diseases have emerged as a global public health concern. Listeria monocytogenes is the one of the foodborne bacteria which cause listeriosis in animals and humans. Contaminated food ingestion is the main transmission route in humans, and it particularly affects newborns, pregnant women, and immunosuppressed and elderly individuals with higher mortality risk. Listeriosis symptoms can vary among patients depending on the infected body part. Diarrhea and fever are the common symptoms of listeriosis, but it is rarely diagnosed. Several L. monocytogenes outbreaks have been associated with contaminated unpasteurized cheese and fresh raw milk consumption. L. monocytogenes environmental presence is ubiquitous in grazing pastures, silage, farmyards, haylage, water, and crop fields. Wild animal feces (rooks and gulls) are important pathogen vectors of farm animal infections. Milking lines (utensils, collectors, filters, and bulk tanks) are also prone to bacterial infections. L. monocytogenes biofilms enhance their survivability in humid environments and their elimination from floor and equipment becomes difficult leading to a higher probability of milk contamination in farms. This review elaborates on the virulence factors, pathogenesis, and the infection cycle of L. monocytogenes. Besides, we will display the various sources of L. monocytogenes contaminations in farm ruminants, transmission vectors, and analyze applicable therapeutic and control measures at each stage.